Β‐Selective Aroylation of Activated Alkenes by Photoredox Catalysis. (17th April 2019) - Lei, Zhen; Banerjee, Arghya; Kusevska, Elena; Rizzo, Eric; Liu, Peng; Ngai, Ming‐Yu
Abstract: Late‐stage synthesis of α, β‐unsaturated aryl ketones remains an unmet challenge in organic synthesis. Reported herein is a photocatalytic non‐chain‐radical aroyl chlorination of alkenes by a 1, 3‐chlorine atom shift to form β‐chloroketones as masked enones that liberate the desired enones upon workup. This strategy suppresses side reactions of the enone products. The reaction tolerates a wide array of functional groups and complex molecules including derivatives of peptides, sugars, natural products, nucleosides, and marketed drugs. Notably, addition of 2, 6‐di‐ tert ‐butyl‐4‐methyl‐pyridine enhances the quantum yield and efficiency of the cross‐coupling reaction. Experimental and computational studies suggest a mechanism involving PCET, formation and reaction of an α‐chloro‐α‐hydroxy benzyl radical, and 1, 3‐chlorine atom shift. Abstract : Kompatibel : Eine photokatalytische β‐selektive Alken‐Aroylierung setzt leicht verfügbare Aroylchloride und aktivierte Alkene ein. Die Reaktion ist mit diversen funktionellen Gruppen kompatibel und zeichnet sich durch hohe Chemo‐ und Regioselektivitäten aus. Sie bietet sich daher für Anwendungen in späten Synthesestadien an, z. B. zur Derivatisierung von Zuckern, Peptiden, Naturstoffen, Nukleosiden und Wirkstoffen.